Case report: Acute hepatitis in neonates with COVID-19 during the Omicron SARS-CoV-2 variant wave: a report of four cases - Wang, Jing; Hu, Wei; Wang, Kexin; Yu, Rong; Chang, Liwen; Rong, Zhihui (Frontiers in Pediatrics, 2023)
Background Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), first emerging in December 2019 and continuously evolving, poses a considerable challenge worldwide. It was reported in the literature that neonates had mild upper respiratory symptoms and a better outcome after Omicron SARS-CoV-2 variant infection, but there was insufficient data about complications and prognosis. Case Presentation In this paper, we present the clinical and laboratory characteristics of four Covid-19 neonate patients with acute hepatitis during the Omicron SARS-CoV-2 variant wave. All patients had a clear history of Omicron exposure and were infected via contact with confirmed caregivers. Low to moderate fever and respiratory symptoms were the primary clinical manifestations, and all patients had a normal liver function at the initial stage of the course. Then, the fever lasted 2-4 days, and it was noted that hepatic dysfunction might occur 5-8 days after the first onset of fever, mainly characterized by moderate ALT and AST elevation (>3-10 fold of upper limit) and without abnormalities in bilirubin level, blood ammonia, protein synthesis, lipid metabolism, and coagulation. All the patients received hepatoprotective therapy, and transaminase levels gradually decreased to the normal range after 2-3 weeks without other complications. Conclusions This is the first case series about moderate to severe hepatitis in COVID-19 neonatal patients via horizontal transmission. Besides fever and respiratory symptoms, the clinical doctor should pay much attention to evaluating the risk of liver function injury after SARS-CoV-2 variants infection, which is usually asymptomatic and delayed onset.